CORRELATION BETWEEN SOCIAL SUPPORT OF FAMILY WITH WORK-FAMILY CONFLICT ON WOMEN WORKERS OF WOVEN SARONG FACTORY IN PEKALONGAN - Perdana, Mukhammad Rangga; Nurtjahjanti, Harlina (Empati, 2014)
The purpose of this study was to determine how the relationship between social support families with work-family conflict on women workers of woven sarong factory in Pekalongan. Social support of family is the support given by family of her husbandd and children to subject, while work-family conflict is a situation that caused a conflict between the demands of work and family roles. Subjects were women workers of cone winder in production of Pismatex and Pajitex factory. The sampling technique that used in this research is Cluster random sampling and the result is 90 sample in Pismatex factory. Data retrieval of this research using social support of family scale (35 valid item with Î±=0.862) and work-family conflict scale (26 valid item with Î±=0.834) that tested to 49 women workers of cone winder of Pajitex factory in Pekalongan. Research data obtained from the result of simple regression analysis showed that coefficient correlation is -0.448 with p=0.00 (p